Pengaruh Penerapan Sistem Informasi Akuntansi Pemanfaatan Teknologi Informasi dan Kualitas SDM terhadap Peningkatan Kinerja Karyawan (Studi Kasus Pada BUM Desa Di Kabupaten Rejang Lebong) - Tuti Hermalinda; Berlian Afriansyah; Meriana Meriana (Universitas Muhammadiyah Metro, 2021)
This study aims to determine the extent to which the application of accounting information systems, the use of quality information technology and human resources will affect the improvement of employee performance. This study uses a statistical test, namely the hypothesis test either partially or simultaneously with the t test and the F test. Data collection using a Likert scale questionnaire with the number of respondents as many as 180 employees of BUM Desa in Rejang Lebong Regency. The results showed that there was a significant influence between the variables of the Accounting Information System, Information Technology and Human Resources on the Performance of BUM Desa Employees.